Identification of Immune Hub Genes Associated With Braak Stages in Alzheimer’s Disease and Their Correlation of Immune Infiltration - Qian, Xiao-hang; Liu, Xiao-li; Chen, Sheng-di; Tang, Hui-dong (Frontiers in Aging Neuroscience, 2022)
Background: Alzheimer's disease (AD) was the most common type of neurodegenerative disease. Tau pathology was one of the pathological features of AD, and its progression was closely related to the progress of AD. Immune system dysfunction was an important mediator of Tau pathological progression, but the specific molecular mechanism was still unclear. The purpose of this study was to determine the immune central genes and peripheral immune cell infiltration associated with the Braak stages, and the molecular mechanisms between them. Methods: Sixty samples with different Braak stages in GSE106241 dataset were used to screen Braak stages related immune hub genes by WGCNA and cytoHubba. The temporal lobe expression data in Alzdata database were used to verify the results. Correlation analysis of immune hub genes with pathological features of AD. CIBERSORT was used to evaluate the abundance of peripheral immune cell infiltration and screened Braak stages-related cells. Finally, we used correlation analysis of immune hub genes and immune cells, and Gene Set Enrichment Analysis (GSEA) of them. Results: Eight genes (GRB2, HSP90AA1, HSPA4, IGF1, KRAS, PIK3R1, and PTPN11) were identified as immune core genes after screening of test dataset and validation of independent data. Among them, KRAS and PIK3R1 were the most closely related to Tau and Aβ pathology in AD. In addition, the immuneScore increased gradually with the increase of Braak stages. Five types of immune cells (plasma cells, T follicular helper cells, M2 macrophage, activated NK cells, and eosinophils) were correlated with Braak stages. KRAS and PIK3R1 were the immune core genes most related to the abnormal infiltration of peripheral immune cells. They participated in the regulation of the pathological process of AD through axon guidance, long term potentiation, cytokine cytokine receptor interaction, RNA polymerse, etc. Conclusions: KRAS and PIK3R1 were identified as the immune hub genes most associated with Tau pathological progress in AD. The abnormal infiltration of peripheral immune cells mediated by them was involved in Tau pathological process. This provides provide new insights for AD.